Nurses' perceived preparedness of knowledge and skills in caring for patients attacked by Tsunami in Banda Aceh, Indonesia and its related factors - Dewi Hermawati (Prince of Songkla University, 2012)
Thesis (M.Sc, Nursing Science)--Prince of Songkla University, 2010